Overview of the Translation, Dissemination, and Implementation of Public Health Preparedness and Response Research and Training Initiative - Qari, Shoukat H. (Am J Public Health, 2018)
We provide an overview of a Centers for Disease Control and Prevention–funded public health preparedness and response (PHPR) research and training initiative to improve public health practice. Our objectives were to accelerate the translation, dissemination, and implementation (TDI) of promising PHPR evidence-based tools and trainings developed by the Preparedness and Emergency Response Research Centers (PERRC) or the Preparedness and Emergency Response Learning Centers (PERLC) between 2008 and 2015. Nine competitive awards were made to seven academic centers to achieve predetermined TDI objectives. The outputs attained by the initiative included: user-friendly online repositories of PERRC and PERLC tools and trainings; training courses that addressed topics; a community resilience manual to synthesize, translate, and implement evidence-based programs; and Web applications that supported legal preparedness, exercise evaluation, and immunization education. The evaluation identified several best practices and potential barriers to implementation. As illustrated by the work in this supplement, the broader awareness and implementation of PERRC preparedness products and PERLC trainings and the continued evaluation of their impact could enhance the PHPR capacity and capability of the nation, which could lead to improved health security.